The renovation of urban planning (Ciudades, 2018)
The real present scene of diffuse and changing cities shows the actual crisis of the traditional urban planning as a suitable instrument for the definition and control of development. The disregulating positions in which the market policy is prioritary over an obsolete planning drive to a non-sustainable development, and it’s neccesary to harmonize economical efficiency and social equity. This text analyzes the traditional planning crisis and its roots, in a context of a new territoriality and social organization, and sets up its renovation as a basic instrument in both spheres, urban and territorial. It is clearly shown that a new planning context is neccesary, which should be strategical, conceived from the distinction between Master plans (structural, global plans) and Action plans (operational plans embodied into those ones), with sensible different temporal and management extent.
Keywords: diffuse city; urban planning; strategical plan; planning-by-doing; master and operational plan